Educação de Jovens e Adultos e as políticas públicas educacionais : mapeamento da produção bibliográfica na base SciELO (2015-2020) - Coelho, Andréia Batista (2021)
This is a bibliographical research in the line of Teacher Training and Educational Public Policies that encourages a discussion about Youth and Adult Education. A conceptual analysis is carried out based on the following question: What are the contributions of scientific research from the Scielo base on teacher education policies in EJA (2015-2020)? For this, based on the Communicative Methodology from the following descriptors: EJA, Youth and Adult Education, Teacher Training Policies and Educational Public Policies, an analysis called between-texts was built in order to identify what scientific publications bring of excluding and transforming elements on public educational policies for teacher training in EJA. During the investigation, it was observed that the fight movements in the Mundo da Vida are fundamental for the provocation of the process of construction of State public policies. We also emphasize the importance of the role of public universities in seeking to fill spaces and establish dialogical communicative relationships between the public spheres, civil society, the scientific community and popular struggle in order to foster debates and pave solid paths for the implementation of educational public policies. Thus, teacher training in the modality can be a provocative path for the public sphere to assume the complexity of EJA and its specificities as a public policy of the State.